2020
DOI: 10.1021/acssynbio.0c00305
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of Rapid Optogenetic Circuits for Dynamic Control in Yeast Metabolic Engineering

Abstract: The use of optogenetics in metabolic engineering for light-controlled microbial chemical production raises the prospect of utilizing control and optimization techniques routinely deployed in traditional chemical manufacturing. However, such mechanisms require well-characterized, customizable tools that respond fast enough to be used as real-time inputs during fermentations. Here, we present OptoINVRT7, a new rapid optogenetic inverter circuit to control gene expression in Saccharomyces cerevisiae. The circuit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 49 publications
1
67
0
Order By: Relevance
“…Different blue-light optogenetic systems have been implemented in yeast to control gene expression, with remarkable applications in metabolic engineering and yeast biotechnology [8][9][10][11][12]. Among them, the OptoEXP and OptoINVRT optogenetic systems, both based on the blue-light photoreceptor EL222 from Erythrobacter litoralis, have been used to redirect the glycolytic metabolic flux depending on the applied light or dark regimens [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Different blue-light optogenetic systems have been implemented in yeast to control gene expression, with remarkable applications in metabolic engineering and yeast biotechnology [8][9][10][11][12]. Among them, the OptoEXP and OptoINVRT optogenetic systems, both based on the blue-light photoreceptor EL222 from Erythrobacter litoralis, have been used to redirect the glycolytic metabolic flux depending on the applied light or dark regimens [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Biosynthesis of isobutanol in yeast is challenged by the strong competition with ethanol biosynthesis, a pathway that cannot be easily deleted genetically due to its essential role for growth on glucose [ 54 , 55 ]. We have previously shown that this challenge can be overcome by dynamically controlling the ethanol and the mitochondrial isobutanol biosynthetic pathways with light using optogenetic circuits [ 56 , 57 ]. The two pathways compete for pyruvate, metabolized by either pyruvate decarboxylases (encoded by PDC1, PDC5 and PDC6 ) for ethanol production or by acetolactate synthase (encoded by ILV2 ) for isobutanol.…”
Section: Resultsmentioning
confidence: 99%
“…6 a). By controlling PDC1 (in a strain with the three native PDC genes knocked out) using a light-activated circuit (OptoEXP) [ 57 ], and ILV2 with a dark-activated circuit (OptoINVRT7) [ 56 ], the engineered yeast can grow only in the light (producing ethanol), and then direct its metabolic flux towards isobutanol production in the dark (Fig. 6 a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations